The Influence of the TPACK based Inquiry Teaching Model on Student's Critical Thinking Skills - Mia Aina; Everhard Markiano Solissa; Venty Sopacua; Elismayanti Rembe; Andri Kurniawan; Muhammad Nur; Bambang Mardi Sentosa; Tomi Apra Santosa; Aat Ruchiat Nugraha (Edumaspul: Jurnal Pendidikan, 2024)
The purpose of the study was to determine the effect of tpack-based inquiry teaching model on students' critical thinking skills. This research is a type of meta-analysis research. The data sources in this study came from the analysis of 15 national and international journals published in 2021-2024. The inclusion criteria in the study are that the research must be indexed by Sinta and Scopus, the research comes from open access journals, the research has a relationship with the research variables, the research data is accessed through the Google Scholar Journal Database, Wiley, Taylor of Francis, Mendeley and Researhgate and the research must attach sticky data to calculate the effect size value. Data collection techniques are direct observation and documentation. Data analysis is quantitative analysis by calculating the effect size value with JSAP software. the results concluded that the tpack-based inquiry teaching model had a significant effect on students' critical thinking skills with a value of res = 0.914; P < 0.001. this finding provides positive information for teachers to implement this model in learning